Stacking fault energy of face-centered-cubic high entropy alloys. (February 2018) - Liu, S.F.; Wu, Y.; Wang, H.T.; He, J.Y.; Liu, J.B.; Chen, C.X.; Liu, X.J.; Wang, H.; Lu, Z.P.
Abstract: The stacking fault energy (SFE) values of several typical face-centered-cubic (fcc) high-entropy alloys (HEAs) were experimentally measured by weak-beam dark-field transmission electron microscopy. It was found that the SFE of the Fe-Co-Ni-Cr-Mn HEA system strongly depends on the SFE of the individual constituents. Specifically, the SFE of this HEA system is closely associated with the Ni concentration in the alloys. Additionally, the lower SFE tends to promote formation of more deformation twins with a smaller thickness under loading, leading to better mechanical properties, especially at low temperatures. Highlights: SFE of six Fe-Co-Ni-Cr-Mn HEAs was measured experimentally. Constituents play an important role in the SFE, particularly the Ni content. Lower SFE promotes formation of thinner twins during loading and better properties.